International Faculty in Japan - Huang, Futao (International Higher Education, 2018)
The 1979 and 2017 national surveys of full-time international faculty at Japanese universities show numerous important changes. The proportion of female academics has increased, and Japanese universities hire more international faculty in high academic positions, doing research in the hard sciences, and originating from China and Korea. Today, the vast majority of international faculty come to Japan for academic reasons, and have more positive perceptions of the Japanese academic market and their Japanese colleagues.